2020
DOI: 10.1177/1756284820931738
|View full text |Cite
|
Sign up to set email alerts
|

Biologics and surgical outcomes in Crohn’s disease: is there a direct relationship?

Abstract: Despite significant advances in medical therapy in the management of Crohn’s disease (CD), surgery is still required in a significant proportion of patients and constitutes an important tool in treatment algorithms. Recently, more options of biological agents have been made available, and most patients with CD undergoing surgical procedures have been previously exposed to this class of drugs. There is controversy in the literature as to whether anti-tumor necrosis factor (TNF) agents, anti-integrins, or anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 58 publications
(113 reference statements)
0
26
0
Order By: Relevance
“…The preliminary data of several meta-analyses showed a higher risk of complications in IBD patients treated with anti-TNF, especially in those with CD [24,25]. In contrast to these data, the administration of preoperative infliximab was not related to the appearance of early postoperative complications in recent meta-analyses for CD [26,27]. Furthermore, the only two studies that evaluated this effect prospectively showed that neither anti-TNF administration nor anti-TNF drug levels during the preoperative period was associated with postoperative complications in IBD; therefore, the complete withdrawal of biological therapy during the preoperative period is not necessary to reduce the frequency of postoperative complications [28,29].…”
Section: Discussionmentioning
confidence: 89%
“…The preliminary data of several meta-analyses showed a higher risk of complications in IBD patients treated with anti-TNF, especially in those with CD [24,25]. In contrast to these data, the administration of preoperative infliximab was not related to the appearance of early postoperative complications in recent meta-analyses for CD [26,27]. Furthermore, the only two studies that evaluated this effect prospectively showed that neither anti-TNF administration nor anti-TNF drug levels during the preoperative period was associated with postoperative complications in IBD; therefore, the complete withdrawal of biological therapy during the preoperative period is not necessary to reduce the frequency of postoperative complications [28,29].…”
Section: Discussionmentioning
confidence: 89%
“…In conclusion, direct cause–effect relationship of biologics alone leading to increased rates of complications was not demonstrated and different studies results are controversial [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that different confounding factors can impact the rates of postoperative complications after colectomy in patients with UC. The most important are the previous use of corticosteroids, an impaired nutritional status, and unfavorable systemic conditions, such as anemia [ 2 , 50 ]. Overall, most patients undergoing colectomy for UC are already using biological agents at the moment of surgery, and more than one of these factors may also be additionally present.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is an important tool in the current therapeutic armamentarium, and is still needed in a significant proportion of patients with UC [ 1 ]. Colectomy represents a great challenge to the surgeon due to the severity of the disease and associated disease-related factors, such as malnutrition, infections, anemia, and previous use of corticosteroids [ 2 ]. Currently, most patients undergoing an elective colectomy for UC have usually been previously exposed to some type of biological agent [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation